The Trauma of Post-1998 Indonesian Horror Films - Barker, Thomas (Journal of Letters, 2016)
In the decade following the end of the New Order regime in 1998; feature film making in Indonesia returned to both productivity and popularity after a hiatus in the 1990s. Significantly; a third of all films produced over the last decade have been horror films. Almost all of these horror films have deployed the familiar kuntilanak ghost; a grotesque avenging female spirit whose desire for justice propels the film’s narrative. Whilst these horror films have been popular with audiences; critics have dismissed them as cheap; commercial; derivative and simplistic. In this paper I argue that when post-1998 horror films are subjected to greater scrutiny; they reveal an insight into what haunts contemporary Indonesian society. By closely analyzing the narrative structure of these films; a temporal gap is evident between the original violent incident (rape; murder; suicide; generally ‘crimes of passion’) and the reappearance of the ghost. Typically the ghost lies dormant until disturbed by a group of unsuspecting Jakartan youths who then become entangled in her search for justice. In horror films pre-1998; neither this temporal gap existed nor did the mediating role played by youths. By drawing on psychoanalytical film theory that analyses how horror films represent widely held social anxieties; I suggest that the popularity of horror films in post 1998 Indonesia indicates a broadly felt trauma about the unresolved violence of the New Order regime. At the visceral level; these stories of horror provide catharsis for audiences in post 1998 Indonesia through the re-enactment of the violence in the genre of horror. My analysis of these films also reveals a relationship between popular film; contemporary audiences and historical trauma. บาดแผลฝังจำในภาพยนตร์สยองขวัญอินโดนีเซียหลังปี 1998 โธมัส บาร์คเกอร์* * นิสิตปริญญาเอก มหาวิทยาลัยแห่งชาติสิงคโปร์ (National University of Singapore) ในช่วงหนึ่งทศวรรษหลังสิ้นสุดการปกครองของยุคระเบียบใหม่ (the New Order) เมื่อ ค.ศ. 1998 การสร้างภาพยนตร์ขนาดยาวในอินโดนีเซียกลับมาเฟื่องฟูและได้รับความนิยม อีกครั้งหลังจากหยุดชะงักในช่วงทศวรรษ 1990 น่าสังเกตว่าหนึ่งในสามของภาพยนตร์ทั้งหมดที่ถูกผลิตในช่วงสิบกว่าปีที่ผ่านมานั้นเป็นภาพยนตร์สยองขวัญ ซึ่งภาพยนตร์แนวนี้เกือบทั้งหมดใช้ผี กุนทิลานัก (kuntilanak) ในการดำเนินเรื่องเล่าของภาพยนตร์ โดยผี กุนทิลานัก นั้นเป็นที่รู้จักกันดีในฐานะวิญญาณหญิงพยาบาทผู้มาเรียกร้องขอความเป็นธรรม อย่างไรก็ตาม ขณะที่ภาพยนตร์สยองขวัญเหล่านี้ได้รับความนิยมจากผู้ชม บรรดานักวิจารณ์กลับไม่ให้ความสนใจ เนื่องจากมองว่าภาพยนตร์เหล่านี้เป็นภาพยนตร์เกรดต่ำ มุ่งหวังแต่ผลกำไร ดาษดื่น และไม่มีความซับซ้อน ในบทความนี้ผู้วิจัยต้องการชี้ให้เห็นว่าหากพิจารณารายละเอียดของภาพยนตร์ สยองขวัญหลังปี ค.ศ. 1998 อย่างลึกซึ้ง จะพบว่าภาพยนตร์เหล่านี้ช่วยเปิดเผยให้เข้าใจถึงสิ่งที่หลอกหลอนสังคมอินโดนีเซียร่วมสมัย การวิเคราะห์โครงสร้างเรื่องเล่าของภาพยนตร์อย่างละเอียดแสดงให้เห็นรอยแยกชั่วคราวที่ชัดเจนระหว่างเหตุการณ์ความรุนแรงที่เกิดขึ้น (อาทิ การข่มขืน ฆาตกรรม การฆ่าตัวตาย หรืออาชญากรรมทั่วไปที่เกิดจากความรักความหึงหวง) กับการปรากฏตัวซ้ำของผี ซึ่งโดยปกติผีจะอยู่อย่างสงบจนกระทั่งถูกรบกวนจากกลุ่มเด็กวัยรุ่นชาวจาการ์ตาที่ต้องเข้ามาพัวพันกับการแสวงหาความยุติธรรมของผีด้วยความรู้เท่าไม่ถึงการณ์ อย่างไรก็ตาม รอยแยกชั่วคราวดังกล่าวหรือการรับบทบาทเป็นสื่อกลางของวัยรุ่นกลับไม่ปรากฏในภาพยนตร์สยองขวัญก่อนปี ค.ศ. 1998 ในการนำทฤษฎีภาพยนตร์เชิงจิตวิเคราะห์เข้ามาวิเคราะห์ว่าภาพยนตร์สยองขวัญเป็นภาพแทนของความวิตกกังวลที่แพร่หลายในสังคมได้อย่างไรนั้น ผู้วิจัยเสนอว่าความนิยมภาพยนตร์สยองขวัญในอินโดนีเซียช่วงหลังปี ค.ศ. 1998 ชี้ให้เห็นบาดแผลฝังจำ (trauma) ที่รู้สึกร่วมกันในวงกว้างเกี่ยวกับความรุนแรงของการปกครองในยุคระเบียบใหม่ที่ยังไม่คลี่คลาย เมื่อพิจารณาในแง่ของสัญชาตญาณ เรื่องราวสยองขวัญเหล่านี้ช่วยให้ผู้ชมยุคหลังปี ค.ศ. 1998 ปลดปล่อยอารมณ์ความรู้สึกผ่านทางความรุนแรงที่เกิดขึ้นซ้ำในภาพยนตร์แนวดังกล่าวด้วยเหตุนี้ การศึกษาวิเคราะห์ภาพยนตร์สยองขวัญจึงแสดงให้เห็นความสัมพันธ์ระหว่างภาพยนตร์ยอดนิยม ผู้ชมร่วมสมัย และบาดแผลฝังจำทางประวัติศาสตร์